Effect of Activation Time on Physicochemical Properties of Activated Carbon Prepared from Coconut Shell - Zakariah A. ADEJOH; Hawawu SALAMI; Abdullahi M. EVUTI; Yahaya S. MOHAMMAD; Yakubu STEPHEN (FUDMA Journal of Engineering and Technology, 2025)
The Characteristics of activated carbon derived from coconut shells (CS) are influenced by the activation process parameters, which include activation temperature, time, and the application of different activation agents. This study intends to evaluate the impact of activation time on the physicochemical properties of activated carbon produced from coconut shells. Coconut shells were used as a precursor to prepare activated carbon, with phosphoric acid serving as the activation agent. Different samples were prepared using activation times of 6, 12, and 24 hours, with a carbonization temperature of 500 °C for 60 minutes. The prepared activated carbon samples were characterized using a gas sorption analyzer, SEM, and FT-IR. The activated carbon’s specific surface area increased from 189 to 505.8 m2/g, and micropore volume increased from 0.146 to 0.311 cm3/g, as the activation time was extended from 6 to 24 hours, respectively. This property improvement was also confirmed by SEM and FTIR. The FTIR analysis depicts the presence of different functional groups. In conclusion, the properties of the prepared activated carbon are affected by the activation time.  The results confirmed that coconut shell is a promising low-cost precursor for activated carbon production, which is useful for environmental applications.
Keywords: Coconut shell, activated carbon, surface area, SEM/EDX, FTIR.